An Empirical Exploration Into the Measurement of Rape Culture - Johnson, Nicole L. (Journal of interpersonal violence, 2021)
Feminist scholars have long argued the presence of a “rape culture” within the United States; however, limited efforts have been made to quantify this construct. A model of rape culture was first proposed in 1980 and expanded in the 1990s in an effort to quantify rape myth acceptance. This model posits that five underlying components make up a rape culture: traditional gender roles, sexism, adversarial sexual beliefs, hostility toward women, and acceptance of violence. Although these components are proposed as cultural phenomenon and thus distinct from individually held beliefs, they have been exclusively explored on an individual level. Thus, to promote exploration of this phenomenon beyond individually held beliefs, the authors adapted a series of well-established measures to assess the perceived peer support of the constructs proposed to underlie rape culture and assess initial reliability and validity in a sample of 314 college students. Following determination of reliability and validity of these adapted measures, a hierarchical confirmatory factor analysis was run to examine the proposed model of rape culture. Results of this study highlight the uniqueness between individual and cultural factors as several items did not translate from an individual (i.e., personal endorsement) to a cultural level (i.e., perceived peer support) and were subsequently removed from the proposed final measurements. Furthermore, initial support for the aforementioned model of rape culture was identified. These findings are crucial given that limited conclusions may be drawn about the existence and in turn eradication of rape culture without an agreed upon definition and source of measurement.